Social perception of the nursing profession - FRANCO COFFRE, JOICY ANABEL (2019)
The social perception that a profession has is directly related to what the professional transmits of his own identity. In the specific case of nursing, he carries on his shoulders a historical burden that, instead of giving him prestige, gave him stigmata, such as: the use of uniform, the nursing exercise as punishment (payment of sins) and the beginning of the Professionalization with Florence Nightingale. A bibliographic review was carried out in databases Scielo, Google Scholar, Virtual Health Library of the WHO, with the boolean terms of "social perception" "nursing" "professional identity" and 34 scientific articles of type review or reflection were obtained ; articles of less than 5 years that respond to the search and interest of the author were selected. As a result, it was obtained that nursing as a profession has stigmas such as weakness, invisibility, poor autonomy, unfair remuneration, sex toys and other stereotypes. It is concluded that, although the mistaken beliefs of nursing are intricate in the population, the nurse is the only one in charge of building a solid professional identity, which will be transmitted to society.